# |
ODE |
Mathematica |
Maple |
\[
{}2 \sqrt {x y}-y-x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = {\mathrm e}^{\frac {x y^{\prime }}{y}}
\] |
✓ |
✓ |
|
\[
{}2 y^{2} x^{3}-y+\left (2 x^{2} y^{3}-x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y-1-x y+x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }-y = x \tan \left (\frac {y}{x}\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\frac {y}{x} = {\mathrm e}^{x y}
\] |
✓ |
✓ |
|
\[
{}y y^{\prime \prime }-y y^{\prime } = {y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}2 y-x \left (\ln \left (x^{2} y\right )-1\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {1}{x y+x^{3} y^{3}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {2 \left (y+2\right )^{2}}{\left (x +y-1\right )^{2}}
\] |
✓ |
✓ |
|
\[
{}{\mathrm e}^{x}+3 y^{2}+2 x y y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x y+2 x^{3} y+x^{2} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x {y^{\prime }}^{2}-2 y y^{\prime }+4 x = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime } = 2 \left (y^{\prime \prime }-1\right ) \cot \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y+3 y^{2} x^{4}+\left (x +2 x^{2} y^{3}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = y+\sqrt {x^{2}-y^{2}}
\] |
✓ |
✓ |
|
\[
{}2 y \left (x \,{\mathrm e}^{x^{2}}+y \sin \left (x \right ) \cos \left (x \right )\right )+\left (2 \,{\mathrm e}^{x^{2}}+3 y \sin \left (x \right )^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\cos \left (y\right )+\sin \left (y\right ) \left (x -\sin \left (y\right ) \cos \left (y\right )\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{3}+\left (3 x^{2}-2 x y^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\left (1+y^{\prime }\right ) \ln \left (\frac {x +y}{x +3}\right ) = \frac {x +y}{x +3}
\] |
✓ |
✓ |
|
\[
{}2 x^{3} y y^{\prime }+3 x^{2} y^{2}+7 = 0
\] |
✓ |
✓ |
|
\[
{}x -y \cos \left (\frac {y}{x}\right )+x \cos \left (\frac {y}{x}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} \left (x y^{\prime }-y\right ) = y \left (x +y\right )
\] |
✓ |
✓ |
|
\[
{}y^{4}+x y+\left (x y^{3}-x^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x^{2}+3 \ln \left (y\right )-\frac {x y^{\prime }}{y} = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime } = x +y^{\prime }
\] |
✓ |
✓ |
|
\[
{}y+\left (x y-x -y^{3}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y+2 y^{3} y^{\prime } = \left (x +4 y \ln \left (y\right )\right ) y^{\prime }
\] |
✓ |
✓ |
|
\[
{}y \ln \left (x \right ) \ln \left (y\right )+y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 x^{{3}/{2}}+x^{2}+y^{2}+2 y \sqrt {x}\, y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 x +y \cos \left (x y\right )+x \cos \left (x y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y y^{\prime \prime }-y^{\prime } y^{2}-{y^{\prime }}^{2} = 0
\] |
✓ |
✓ |
|
\[
{}2 y^{\prime }+x = 4 \sqrt {y}
\] |
✓ |
✓ |
|
\[
{}2 {y^{\prime }}^{3}-3 {y^{\prime }}^{2}+x = y
\] |
✗ |
✓ |
|
\[
{}y^{\prime }-6 x \,{\mathrm e}^{x -y}-1 = 0
\] |
✓ |
✓ |
|
\[
{}\left (1+y^{2}\right ) y^{\prime \prime }+{y^{\prime }}^{3}+y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y \sin \left (x \right )+\cos \left (x \right )^{2}-y^{\prime } \cos \left (x \right ) = 0
\] |
✓ |
✓ |
|
\[
{}y \left (6 y^{2}-x -1\right )+2 x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } \left (x -\ln \left (y^{\prime }\right )\right ) = 1
\] |
✓ |
✓ |
|
\[
{}\left (1+\cos \left (x \right )\right ) y^{\prime }+\sin \left (x \right ) \left (\sin \left (x \right )+\sin \left (x \right ) \cos \left (x \right )-y\right ) = 0
\] |
✓ |
✓ |
|
\[
{}x +\sin \left (\frac {y}{x}\right )^{2} \left (-x y^{\prime }+y\right ) = 0
\] |
✓ |
✓ |
|
\[
{}2 x y^{4} {\mathrm e}^{y}+2 x y^{3}+y+\left (x^{2} y^{4} {\mathrm e}^{y}-x^{2} y^{2}-3 x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x y^{3}-1+y^{2} y^{\prime } x^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-2 y^{\prime \prime }+y^{\prime }-2 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+y^{\prime \prime }+9 y^{\prime }+9 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+y^{\prime \prime }-y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+8 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-8 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+18 y^{\prime \prime }+81 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-4 y^{\prime \prime }+16 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-2 y^{\prime \prime \prime }+2 y^{\prime \prime }-2 y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-5 y^{\prime \prime \prime }+5 y^{\prime \prime }+5 y^{\prime }-6 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\left (5\right )}-6 y^{\prime \prime \prime \prime }+9 y^{\prime \prime \prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\left (6\right )}-64 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+6 y^{\prime }+10 y = 3 x \,{\mathrm e}^{-3 x}-2 \,{\mathrm e}^{3 x} \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-8 y^{\prime }+17 y = {\mathrm e}^{4 x} \left (x^{2}-3 x \sin \left (x \right )\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime }+2 y = \left (x +{\mathrm e}^{x}\right ) \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y = \sinh \left (x \right ) \sin \left (2 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }+2 y = \cosh \left (x \right ) \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+y^{\prime } = \sin \left (x \right )+x \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-2 y^{\prime \prime }+4 y^{\prime }-8 y = {\mathrm e}^{2 x} \sin \left (2 x \right )+2 x^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-4 y^{\prime \prime }+3 y^{\prime } = x^{2}+{\mathrm e}^{2 x} x
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+2 y^{\prime \prime } = 7 x -3 \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+5 y^{\prime \prime }+4 y = \sin \left (x \right ) \cos \left (2 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\left (5\right )}-3 y^{\prime \prime \prime }+y = 9 \,{\mathrm e}^{2 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-3 y^{\prime \prime }+3 y^{\prime }-y = 48 x \,{\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-3 y^{\prime } = 9 x^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\left (5\right )}+4 y^{\prime \prime \prime } = 7+x
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y^{\prime }-2 y = 36 \,{\mathrm e}^{2 x} x
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+16 y = 64 \cos \left (2 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+4 y^{\prime \prime }-y = 44 \sin \left (3 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+y^{\prime \prime }+5 y^{\prime }+5 y = 5 \cos \left (2 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+3 y^{\prime }+5 y = 5 \,{\mathrm e}^{-x} \sin \left (2 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-y = 4 \,{\mathrm e}^{-x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y = 8 \sin \left (x \right )^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-y^{\prime \prime }+y^{\prime }-y = 4 \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-y^{\prime \prime } = 2 \,{\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 y^{\prime }+4 y = {\mathrm e}^{x} \left (1+x \right )+2 \,{\mathrm e}^{2 x}+3 \,{\mathrm e}^{3 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime }+5 y = 4 \,{\mathrm e}^{x} \cos \left (2 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y = 4 \sin \left (2 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y = 12 \,{\mathrm e}^{x} x^{2}+3 \,{\mathrm e}^{2 x}+10 \cos \left (3 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = 2 \sin \left (x \right )-3 \cos \left (2 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y^{\prime } = {\mathrm e}^{x} \left (x^{2}+10\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 y = 96 x^{2} {\mathrm e}^{2 x}+4 \,{\mathrm e}^{-2 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }+2 y = 5 \cos \left (x \right )+10 \sin \left (2 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime }+2 y = 4 x -2+2 \,{\mathrm e}^{x} \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 y^{\prime }+4 y = 4 x \,{\mathrm e}^{2 x} \sin \left (2 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-y^{\prime \prime }+y^{\prime }-y = 15 \sin \left (2 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+3 y^{\prime \prime }-4 y = 40 \sin \left (2 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-y^{\prime \prime }+y^{\prime }-y = 2 \,{\mathrm e}^{x}+5 \,{\mathrm e}^{2 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-6 y^{\prime \prime }+11 y^{\prime }-6 y = 10 \,{\mathrm e}^{x} \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-2 y^{\prime }-4 y = 50 \sin \left (x \right )+50 \,{\mathrm e}^{2 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-3 y^{\prime \prime }+4 y = 12 \,{\mathrm e}^{2 x}+4 \,{\mathrm e}^{3 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-8 y^{\prime \prime }+16 y = 32 \,{\mathrm e}^{2 x}+16 x^{3}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-18 y^{\prime \prime }+81 y = 72 \,{\mathrm e}^{3 x}+729 x^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y = \frac {1}{x}-\frac {2}{x^{3}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y = \frac {1}{\sinh \left (x \right )}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime }+y = \frac {{\mathrm e}^{x}}{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+3 y^{\prime }+2 y = \sin \left ({\mathrm e}^{x}\right )
\] |
✓ |
✓ |
|